The Impact of the Self-Affirmation Method on the Academic Performance, Stereotype Threat, Stress, and Academic Motivation of Male Pupils in the Third Grade of SecoNdary Schools in Ilam - Yaser Alizadeh; Manijeh Shehni Yailagh; Sirous Allipour Birgani; Gholamhossien Maktabi (پژوهش‌های کاربردی روانشناختی)
The purpose of the current research is to ascertain the impact of the self-affirmation method on the academic performance, stereotype threat, stress, and academic motivation of male pupils in the third grade of secondary schools in Ilam City. This study was conducted as a field experimental design with a pre-test, post-test, and an active control group, and it is applied in terms of its purpose. The statistical population of this study consists of all male pupils who attended public schools in Ilam during the academic year of 2021-2022. Sixty individuals who met the project’s eligibility criteria and achieved a score one standard deviation below the average in the aforementioned test were randomly assigned to one of two experimental and control groups. The pre-test and post-test comprised the Spontaneous Self-Affirmation Measure (SSAM), the Stereotype Threat Experienced Scale (STES), the Depression, Anxiety and Stress Scale-21 (21-DASS), the Academic Motivation Scale (AMS), and Academic Performance. The control group received an ineffective intervention, whereas the experimental group received the self-affirmation intervention. The analysis was conducted with the assistance of SPSS software version 24, utilizing statistical methods such as Multivariate Analysis of Covariance (MANCOVA) and Univariate Analysis of Covariance (ANOVA), with the help of SPSS software version 24. The results showed that the self-affirmation intervention has a significant effect on the academic performance, tension, intrinsic motivation, and extrinsic motivation of students. In this way, self-affirmation yields significant improvements in academic performance and intrinsic motivation, while simultaneously diminishing stereotype threat, stress, and extrinsic motivation.